Nigeria and the transnationalisation of kidnapping in the Lake Chad region and the Gulf of Guinea - Ojo, John Sunday (The political economy of kidnapping and insecurity in Nigeria, 2024)
This chapter explores the transnational nature of the operation of the Nigerian-based kidnappers, that is, coastal militants or pirates in the Gulf of Guinea and Islamist extremists in the Lake Chad region. The expansion of transnational kidnapping orchestrated by the Jihadist terrorist groups such as Boko Haram/ISWAP in northern Nigeria, whose heinous activities have spill-over effects and contagiously impacted neighbouring nations such as Chad, Cameroon and Niger has redefined national sovereignty. The activities of the transnational armed militant and criminal groups in the Niger Delta and other coastal areas of Nigeria have also accounted for significant portion of piracy in the Gulf of Guinea. These among others need to interrogate the idea of nationality and transnationality in this context. Beyond some basic conceptual clarifications and theoretical analysis, this chapter explores the dark side of globalisation as evident in Nigerian-based transnational kidnapping. It pays attention to causes, manifestation, hotspots, implications and possible control of transnational kidnapping, as regards various borders that Nigeria shared with other countries and the international waters, ranging from the North to the South and the East to the West.